Influência da dor lombar crônica inespecífica com ou sem sensibilização central nos aspectos biopsicossociais e capacidade funcional de idosos - Marques, José Salvador Ribeiro (2020)
Nonspecific chronic low back pain (DLCI) is considered one of the main complaints reported by the elderly, leading them to a decline in several biopsychosocial and functional variables. The literature reports that the chronicity of low back pain may be related to impairments in functional capacity and in the psychosocial realm. DLCI can promote changes in the brain's representation of pain, and patients may experience central sensitization (SC), that is, an amplification of neural signaling within the central nervous system causing hypersensitivity to pain. Thus, this study aims to assess the influence of the DLCI of elderly people in the context of social vulnerability and the influence of central awareness on biopsychosocial variables and on the functional capacity of elderly people with DLCI, in addition to describing sociodemographic and health variables such as gender, age , Body mass index (BMI), pain level and total pain areas. The analysis of the general results of our dissertation concludes that the decrease in mobility and balance may be involved with DLCI, in addition, the non-performance of 30 minutes of physical activity daily and the non-performance of physical activity in the community / neighborhood, may have positive influence with DLCI in the elderly in a context of high vulnerability, in addition, CS can influence the decrease in mobility, balance, power and resistance of the lower limbs, decrease in the pain-pressure threshold, increase in the degree of kinesiophobia and catastrophization, worsens of depressive symptoms and decreased quality of sleep in elderly people with DLCI. To this end, two studies were carried out: Study 1: Evaluation of biopsychosocial factors present in elderly people with chronic non-specific low back pain, in a context of high vulnerability Study 2: Influence of central sensitization on biopsychosocial variables and functional capacity in the elderly with chronic nonspecific low back pain